Faculty engagement in community extension programs: Examining personal factors, institutional support, and stakeholder collaboration in a state university - Jaron, Wanny B.; Malaga, Ronora Sevilla (Edelweiss Applied Science and Technology, 2025)
This study explored the institutional, collaborative, and individual elements that affect teacher involvement in community engagement activities at a state university in Central Philippines. Faculty extensionists were used to test the reliability of a survey created by the researcher and validated by experts. It used a parallel convergent mixed-method approach and polled 90 of the 99 eligible faculty members who participated in community involvement between 2020 and 2025. Descriptive and inferential statistics were used to analyze the data, along with Lichtman's 3Cs technique. The results showed that just 27% of faculty members took part in community programs, and individual factors like workload, motivation, and career advancement influenced that participation. Long-term engagement was made feasible by institutional aspects like funding, workload equality, and incentives, as well as collaborative aspects like openness, capacity building, and joint decision-making. To improve involvement, faculty proposed measures such as enhanced institutional support, collaborative governance, more clearly defined roles, and skill development programs. These findings offer important insights for universities seeking to improve faculty involvement in community engagement by addressing institutional supports and barriers.